Pilot Testing for Knowledge, Attitudes, and Practices (KAP) Survey on Cumulative Antibiogram Use Among Healthcare Professionals Managing Immunocompromised Children - Reham Khedr; Mervat Gaber; Whitney Ziegenhorn; Maysam R Homsi; Amal Hosni Mhmoud; Ahmed Kamal Bayoumi; Dilnasheen Safdar; Solomie Deribessa; Neema Kayange; Yousif Madney; Mohamed Abdelhakim; Boniface Masalalipu; et al. (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background The effective use of antibiograms (ABG) is essential for optimizing antimicrobial therapy, particularly in Lower- and Middle- Income Countries (LMIC), where high rates of antimicrobial resistance, limited diagnostics, and resource constraints pose significant challenges. Without structured ABG development and implementation, clinicians lack essential data to guide empirical therapy, leading to inappropriate antibiotic use, treatment failures, and increased resistance.1, 2 Despite their importance in antimicrobial stewardship, ABG utilization in LMICs remains inconsistent. Literature reviews reveal limited emphasis on antibiogram and few studies evaluating their effectiveness as a quality improvement tool. Guidance on best practices for ABG development, interpretation, and integration into clinical decision-making, particularly in pediatric oncology settings, is insufficent.3Addressing these knowledge gaps is vital for improving infection management, supporting antimicrobial stewardship, and informing policy. This study aims to identify key insights into the barriers and facilitators of ABG implementation in LMICs. Methods A cross-sectional, online survey was designed to assess the knowledge, attitudes, and practices (KAP) of those who create cumulative antibiograms and those who use them in different settings treating children with cancer, across the globe, including St. Jude’s Global Infectious Disease Network. Survey content was based on literature, CLSI M39-A4 guidelines, and expert advisors. The 61-item instrument covered demographics, ABG KAP, and educational preferences. Built in Google Forms with anonymous response collection, the survey was piloted within the ABG Working Group from multiple Eastern Mediterranean and African (EMA) institutions to assess clarity and comprehension. The piloted survey feedback was analyzed to inform revisions. Results Eight respondents participated in the pilot: four with ABG access and four without, stratified into microbiologist vs non-microbiologist. Likert scale ratings showed strong agreement on clarity and relevance (68%-93%) across the four domains. Respondents with ABG access indicated balanced coverage of KAP above 75%. Respondents without ABG access and non-microbiologists provided the lowest ratings (68%) citing unclear terminology and sequencing. Relevance of questions scored highest (100%), while balance across domains scored lowest (58%–75%). These findings guided refinements in terminology, question sequencing, and scaling for contextual relevance. Conclusion Pilot testing confirmed overall clarity and relevance, with higher ratings among respondents with ABG access. Lower scores among those without access highlighted the need for simplified terminology and improved sequencing. Revisions enhanced contextual applicability across diverse settings. The finalized survey will be disseminated through the Global Infectious Disease Network, and results will inform educational interventions to strengthen ABG use in LMIC pediatric oncology programs.